Implementation of Student Akhlakul Karimah Development at SMP Muhammadiyah 57 Medan - Vina Ifanka Lubis (-, 2023)
The purpose of making this journal is to explain the planning and implementation of moral development for students at SMP Muhammadiyah 57 Medan. This study uses a descriptive qualitative approach, with data collection using observation and in-depth interviews and documentation. The data analysis technique used is descriptive qualitative analysis. The results showed that the implementation of moral development for students at SMP Muhammadiyah 57 Medan aims to form pious children, get used to having commendable character, always diligent in worship, getting used to being polite and courteous in socializing and being a graceful child in moral excellence in intellectual.